Instrumental Measurements of Water and the Surrounding Space During a Randomized Blinded Controlled Trial of Focused Intention - Luís Carlos Matos MTCM; Sara Cristina Santos MEng; Joel G. Anderson PhD, CHTP; Jorge Machado PhD; Henry Johannes Greten PhD; Fernando Jorge Monteiro PhD (SAGE Publishing, 2017)
The main goal of this work was the assessment of measurable interactions induced by focused intention, frequently used in biofield practices such as Healing Touch and Reiki . Water, as the main component of the human body, was chosen as a model. Intention experiments were performed over 4 different days at a scheduled interval, during which 286 trained biofield practitioners from several countries were instructed to meditate with the intention to change the molecular vibrational state of water samples selected by a blinded operator. The experimental protocol was randomized, blinded, and controlled; the measured variables included Raman spectra and the pH and electrical conductance of the water, as well as the magnetic field and UV-VIS (ultraviolet-visible) radiation near the experimental spot. Although a direct causal relationship cannot be established, some measurements of the water samples, as well as the magnetic field and radiation near the experimental spot, were responsive during the experimental period.